Resiliensi Hutan Adat Tenganan Pegringsingan Menghadapi Tekanan Pariwisata dan Regulasi Negara - Fikri Danang Himawan; Pramudya Bumishambara (JURNAL NAWALA POLITIKA, 2026)
This study analyzes the resilience of Tenganan Pegringsingan Customary Forest against tourism pressure and state regulation. Synthesizing Traditional Ecological Knowledge (TEK), Social Capital, and Ostrom’s Institutional Design, this research employs a qualitative case study to examine the causal-institutional dynamics of resource management. The findings reveal a paradoxical condition: the forest management is internally optimal, supported by high biodiversity and strict customary laws (awig-awig), yet externally vulnerable to legal fragmentation and market commodification. State interventions often create legitimacy crises, while global ecotourism risks eroding sacred values. The study concludes that sustainability requires a "nested enterprises" model in which indigenous institutions are recognized as equal partners in governance. Furthermore, contextual education is essential to prevent the erosion of TEK among the younger generation, ensuring the long-term preservation of this social-ecological system.